REKAYASA PUDING BERBASIS BISKUIT PEMBERIAN MAKANAN TAMBAHAN (PMT) SEBAGAI KUDAPAN ALTERNATIF BAGI IBU HAMIL KEKURANGAN ENERGI KRONIK (KEK)sia - Wahyuni, Rukmana Indah (Jurnal Gizi dan Kesehatan Nusantara, 2023)
The study aims to : (1) determine the characteristics of color, taste, aroma, and texture of the sensory test of biscuit-based Pudding Supplementary Feeding (PMT); (2) determine the nutritional value of the best product from the biscuit-based sensory test for Supplementary Feeding (PMT). The type of research used is an experiment with 3x2 factorial research design which means 6 treatments. The experiment carried out was the modification and proportion of addition of coconut milk and gelatin to the pudding. The results of the Krusskal Wallis test and the Mann Whitney test showed that the proportion of addition of coconut milk and agar had an effect on aroma and texture but had no effect on color and taste. The results of the depiction of the radar diagram with the parameters aroma, color, texture, taste, and overall it can be seen that the best formula is found in pudding with the S3A1 formula, namely the addition of 45% coconut milk and 75% agar-agar because the S3A1 formula has superior radius length than another. The nutritional value of pudding with the best formulation per 100 grams is 147.6 kcal calories, 18.7% carbohydrates, 3.29% protein, and 6.61% fat.